2020
DOI: 10.1186/s13195-020-00706-2
|View full text |Cite
|
Sign up to set email alerts
|

Decline in cognitively complex everyday activities accelerates along the Alzheimer’s disease continuum

Abstract: Background Impairment in daily functioning is a clinical hallmark of dementia. Difficulties with “instrumental activities of daily living” (IADL) seem to increase gradually over the course of Alzheimer’s disease (AD), before dementia onset. However, it is currently not well established how difficulties develop along the preclinical and prodromal stages of AD. We aimed to investigate the trajectories of decline in IADL performance, as reported by a study partner, along the early stages of AD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Previous studies have shown the added clinical value of combining cognitive with IADL measures, as illustrated by the fact that associations between the overall composite combining cognitive and functional abilities and other clinical measures such as quality of life and caregiver burden were mostly driven by the functional component of the composite in individuals with MCI and mild AD dementia 17 ; likewise the detection of change over time in individuals with MCI on the composite was most apparent on the instrumental ADL (IADL) component 34 . Together, these and other findings emphasize the importance of the inclusion of a sensitive IADL measure to capture clinically meaningful decline in prodromal stages of AD 102 . Thus, outcome measures that combine cognitive and functional items may be useful for measuring the totality of disease progression in Stage 3 participants.…”
Section: Evaluating Cognitive Tests For Coa Selection: Challenges And...mentioning
confidence: 81%
See 2 more Smart Citations
“…Previous studies have shown the added clinical value of combining cognitive with IADL measures, as illustrated by the fact that associations between the overall composite combining cognitive and functional abilities and other clinical measures such as quality of life and caregiver burden were mostly driven by the functional component of the composite in individuals with MCI and mild AD dementia 17 ; likewise the detection of change over time in individuals with MCI on the composite was most apparent on the instrumental ADL (IADL) component 34 . Together, these and other findings emphasize the importance of the inclusion of a sensitive IADL measure to capture clinically meaningful decline in prodromal stages of AD 102 . Thus, outcome measures that combine cognitive and functional items may be useful for measuring the totality of disease progression in Stage 3 participants.…”
Section: Evaluating Cognitive Tests For Coa Selection: Challenges And...mentioning
confidence: 81%
“…For trials targeting Stage 3 individuals, combining cognitive with functional outcome measures may provide an effective approach to establish the meaningfulness of treatments, and this has been recommended by regulatory agencies 4,89 . Accumulating evidence indicates that instrumental activities of daily living (IADL) begin to deteriorate before the onset of dementia, 102 and that an MCI diagnosis accompanied by more IADL problems leads to increased risk of developing dementia 103 . Previous studies have shown the added clinical value of combining cognitive with IADL measures, as illustrated by the fact that associations between the overall composite combining cognitive and functional abilities and other clinical measures such as quality of life and caregiver burden were mostly driven by the functional component of the composite in individuals with MCI and mild AD dementia 17 ; likewise the detection of change over time in individuals with MCI on the composite was most apparent on the instrumental ADL (IADL) component 34 .…”
Section: Evaluating Cognitive Tests For Coa Selection: Challenges And...mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings provide further evidence that biological and cognitive factors underlie changes in IADL functioning: We previously found that any decline in IADL functioning was associated with disease severity, i.e., that patients with dementia declined faster than patients with subjective cognitive complaints, 18 and that worse IADL performance was associated with atrophy in the medial temporal lobe. 48 Studies with other IADL measures related changes in IADL to disease stage, 3 amyloid burden, 49 and executive functioning, 50 irrespective of the clinical meaningfulness of changes. In the present work, we show that disease stage, atrophy, and caregiver burden are associated with clinically meaningful changes in everyday functioning.…”
Section: Discussionmentioning
confidence: 99%
“…In early disease monitoring, incremental changes in function are already seen as a meaningful measure. For example, in Alzheimer's disease, the more complex activities, such as managing paperwork, are specifically sensitive to the earliest cognitive changes (Dubbelman et al, 2020) and may be an indicator of cognitive decline when limited. Also, Wilkins et al (2021) support this by showing that everyday preferences are important predictors for older adults with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%